2013
DOI: 10.1055/s-0033-1349108
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Replacement Strategy during a 27-Km Trail Run in Hot and Humid Conditions

Abstract: We evaluated the effects of the fluid replacement strategy on core temperature, heart rate and urine osmolality during a 27-km trail run in tropical climate. 20 well-trained runners completed a 27-km trail race in tropical conditions. They were acclimatized to these conditions. Heart rate was monitored every 5 s, while core temperature and perceived thermal and comfort sensations were recorded before, at the 11(th) km, and just after the end of the race. Water intake, urine osmolality and body mass were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(21 reference statements)
4
7
0
Order By: Relevance
“…Some studies demonstrated that aerobically fit individuals attained significantly greater end-point temperatures than less-aerobically fit ones [ 19 ]. The fact that highly fit runners sustain high core temperatures throughout prolonged competitions [ 20 , 21 ] is in accordance with the present results showing that high performance is related to high core temperature. In this context, it has also been demonstrated that the increase in core temperature is unlikely to be a primary signal to start the anticipatory process [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Some studies demonstrated that aerobically fit individuals attained significantly greater end-point temperatures than less-aerobically fit ones [ 19 ]. The fact that highly fit runners sustain high core temperatures throughout prolonged competitions [ 20 , 21 ] is in accordance with the present results showing that high performance is related to high core temperature. In this context, it has also been demonstrated that the increase in core temperature is unlikely to be a primary signal to start the anticipatory process [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…The mean increase in T° C was only 0.45°C · hr -1 which is very relatively low regarding the environmental conditions and the athletes’ stature. Indeed, although these results agree with those noted for similar time spent running in tropical climate [ 21 ], it has been demonstrated that bigger athletes increased more their core temperature that smaller ones [ 23 ] and the present kayakers were definitively bigger (i.e., a mean of 84.5 kg) than the runners described in the study of Baillot et al [ 21 ]. We thus would have expected higher heat production and consecutive heat accumulation in relation to exercising in hot and humid environment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taken together, these findings reinforce the view that ad libitum hydration is enough for endurance exercise in a hot environment [17, 21, 22, 23]. These results could be surprising if we consider that average-range athletes normally drink at a higher rate than high-level or more trained ones [24, 25]. In a recent study, Hue et al [9] noted quite pronounced differences between internationally ranked competitors who drank a mean 1.1 L, corresponding to 0.35 L · h −1 , and three nationally ranked competitors who drank a mean 2.2 L, corresponding to 0.80 L · h −1 .…”
Section: Discussionsupporting
confidence: 76%